2006
DOI: 10.1002/ejoc.200600094
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of β‐Bromo‐β‐Substituted Dehydroalanines

Abstract: The methyl ester of N-tert-butoxycarbonyl-(Z)-β-bromo-β-(1,2,4-triazol-1-yl)dehydroalanine was prepared by treatment of the methyl ester of N-tert-butoxycarbonyl-(E)-β-(1,2,4-triazol-1-yl)dehydroalanine with N-bromosuccinimide (NBS), followed by Et 3 N. The reactivities of this compound and of our previously synthesized methyl ester of N-tert-butoxycarbonyl-β,β-dibromodehydroalanine towards several nucleophiles were studied, and it was found that these compounds react with oxygen nucleophiles to give the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In dehydroalanine type compounds, free radicals are most probably attacked to the carbon-carbon double bond and the resulting radical adduct is formed easily by the effect of the groups next to the dehydro unit. N,Ndiprotected dehydroalanine derivatives were found excellent substrates of Michael addition reactions by Ferreira et al [25,26,36,37] but the mono-protected derivatives were found relatively poorer Michael acceptors than the other tested compounds [25,26]. There was no significant correlation found between the antioxidant activity results and the Michael acceptor properties of the compounds.…”
Section: Discussionmentioning
confidence: 70%
“…In dehydroalanine type compounds, free radicals are most probably attacked to the carbon-carbon double bond and the resulting radical adduct is formed easily by the effect of the groups next to the dehydro unit. N,Ndiprotected dehydroalanine derivatives were found excellent substrates of Michael addition reactions by Ferreira et al [25,26,36,37] but the mono-protected derivatives were found relatively poorer Michael acceptors than the other tested compounds [25,26]. There was no significant correlation found between the antioxidant activity results and the Michael acceptor properties of the compounds.…”
Section: Discussionmentioning
confidence: 70%
“…Compound Z-3 was obtained by a sequential Michael addition reaction between the methyl ester of the N-(4-toluenesulfonyl)-N-(tertbutoxycarbonyl)dehydroalanine and 1,2,4-triazole, followed by halogenation with NBS and NEt 3 . 12 Compound 4 was obtained after α-addition, β-substitution and β-elimination. The stereochemistry of compound 4 was determined by NOE difference experiments by irradiating the β-CH and observing a NOE enhancement on the =NCH 2 protons.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Continuing our work concerning the synthesis of non-proteinogenic fluorescent amino acids, we decided to prepare three new pyrenylamino acids using as substrates β,β-disubstituted dehydroalanine derivatives and a strategy previously developed by us. 11,12 Recently, we described the synthesis of α-substituted-β,βdibromoalanines from a β,β-dibromodehydroalanine by treatment with oxygen nucleophiles and primary amines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations